Goddesses and the Moon: Images and Symbols of Сuсuteni–Trypillia - Burdo, Nataliia (Archaeologia Lituana, 2022)
Maria Gimbutas devoted three fundamental monographs to the study of the religion of prehistoric Europe and the Goddess who, in her opinion, reigned in the sacred space of the population of Neolithic Europe. She believed that modern European civilization has its origins in the early agricultural societies of the Neolithic period from the 7th to the 3rd millennia BC, which corresponds to the term “Old Europe”. According to the researcher, the Great Triune Goddess, associated with the cycle of “birth, nurturing, growth, death, and regeneration”, played a dominant and all-encompassing role in the religion of Old Europe, the “goddess religion”. The analysis of the pictorial tradition of the Cucuteni–Trypillia cultural complex allows us to assert that, in addition to female characters, probably goddesses, the symbolism of the Moon, lunar cycles and sacred images related to the semantic field of the Moon were of particular importance during near 2000 years.